Implementation of Strengthening Character Education in Realizing Islamic Values In SMPN 01 Kediri - Munifah Munifah; Rohmatul Fajrin; Fartika Ifriqia (Didaktika Religia, 2019)
This article aims to find out the planning, implementation and evaluation of Strengthening Character Education (SCE) in SMPN 01 Kediri in realizing Islamic values. Islamic education is an effort to actualize the attributes of perfection that have been bestowed by Allah to humans. Strengthening Character Education (SCE) is one way to actualize Islamic values through various activities, intra-curricular, extra-curricular, and non-curricular. This article was written based on the results of a qualitative case study. This article concludes that the implementation of SCE in SMPN 01 Kota in realizing Islamic values, in general, has already been carried out and several aspects need to be improved. Planning for SCE activities in realizing Islamic values needs to be developed in several aspects, namely: (1) there is a need to develop SCE objective indicators, (2) additional activities need to be developed to develop the other three characters in SCE, in order to balance the characters in SCE such as integrity, mutual cooperation, and independence, and (3) SCE activities need to be developed through co-curricular activities, bearing in mind that SCE activities are still focused into extra-curricular activities. The implementation of SCE activities in realizing Islamic values requires the role of parents because they are the first education and as supervisors for their children outside of school. It is also found that evaluating SCE activities in realizing Islamic values had not used measurable appraisal instruments, but direct observation instead.